1994
DOI: 10.1111/j.1751-1097.1994.tb05053.x
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin‐derived Transients: A Pulsed Laser and Pulse Radiolysis Study

Abstract: In this paper we report a time-resolved investigation of transients derived from curcumin, which may be intimately involved in the processes leading to its biological activity. Fluorescence and triplet quantum yields are respectively 0.06 and 0.11. The high percentage of internal conversion is proposed to proceed via H-transfer within the thermodynamically favored enol structure of what is formally a 1,3-diketone. The triplet energy (191 +/- 2 kJ mol-1), natural lifetime (1.5 microseconds) and self-quenching r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 46 publications
5
65
1
Order By: Relevance
“…1B). The tendency of the keto↔enol equilibrium to shift toward the enol tautomer in these solvent systems has been confirmed experimentally by Fourier transform infrared spectroscopy (FT-IR) (Kolev et al, 2005), nuclear magnetic resonance spectroscopy (NMR) (Roughley and Whiting, 1973;Unterhalt, 1980;Gorman et al, 1994;Khopde et al, 2000), fluorescence spectroscopy (Khopde et al, 2000;Nardo et al, 2008), and absorption spectroscopy (Khopde et al, 2000;Nardo et al, 2008) as well as computationally (Kolev et al, 2005;Balasubramanian, 2006;Payton et al, 2007;Galano et al, 2009). In nonpolar solvents, the steadystate absorption spectra of curcumin in cyclohexane (Nardo et al, 2008), toluene , benzene (Khopde et al, 2000), and others (Tønnesen et al, 1995) exhibit a concrete red band or shoulder, which has been ascribed to the diketo tautomer (Khopde et al, 2000;Nardo et al, 2008Nardo et al, , 2009.…”
Section: A Curcumin Structure: Implications On Intermolecular Interamentioning
confidence: 90%
See 2 more Smart Citations
“…1B). The tendency of the keto↔enol equilibrium to shift toward the enol tautomer in these solvent systems has been confirmed experimentally by Fourier transform infrared spectroscopy (FT-IR) (Kolev et al, 2005), nuclear magnetic resonance spectroscopy (NMR) (Roughley and Whiting, 1973;Unterhalt, 1980;Gorman et al, 1994;Khopde et al, 2000), fluorescence spectroscopy (Khopde et al, 2000;Nardo et al, 2008), and absorption spectroscopy (Khopde et al, 2000;Nardo et al, 2008) as well as computationally (Kolev et al, 2005;Balasubramanian, 2006;Payton et al, 2007;Galano et al, 2009). In nonpolar solvents, the steadystate absorption spectra of curcumin in cyclohexane (Nardo et al, 2008), toluene , benzene (Khopde et al, 2000), and others (Tønnesen et al, 1995) exhibit a concrete red band or shoulder, which has been ascribed to the diketo tautomer (Khopde et al, 2000;Nardo et al, 2008Nardo et al, , 2009.…”
Section: A Curcumin Structure: Implications On Intermolecular Interamentioning
confidence: 90%
“…The 1 O 2 yields after irradiation of curcumin with resonant visible light are strongly solvent dependent , which indicates that the energy transfer from triplet state curcumin to O 2 proceeds from the b-dicarbonyl moiety. In nonpolar (toluene and benzene) and polar aprotic (acetonitrile) solvents, the quantum yield of 1 O 2 formation is 0.11-0.12 Gorman et al, 1994), whereas in polar protic solvents such as ethanol and iso-propanol as well as in surfactant micelles (sodium dodecyl sulfate and Triton X-100) the quantum yields are approximately 10-fold lower 240 (Wagner, 1976), and curcumin partially adopts a diketo conformation in aprotic solvents (Fig. 1B).…”
Section: •-mentioning
confidence: 99%
See 1 more Smart Citation
“…12,[31][32][33][34] In all cases, these studies focused on excited-state intramolecular hydrogen atom transfer (ESIHT) of curcumin because this phenomenon has been associated with the medicinal properties of other pigment molecules, including hypericin and hypocrellin. [35][36][37][38][39] Two of these studies agree that the fluorescence lifetime of curcumin in methanol has a dominant component with a time constant of roughly 130 ps.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial preparations of curcuminoids usually contain approximately 77%, 17% and 3% of curcumin, demethoxycurcumin and bisdemethoxycurcumin respectively. Several studies in recent years have shown that curcumin has antioxidant, anti-inflammatory, antimicrobial, anti-bacterial, anti-parasitic, anti-mutagen and anticancer properties [5,6]. It is believed that curcumin is a potent agent against many diseases such as anorexia, coughs, diabetes, hepatic disorders, rheumatism and Alzheimer disease [7][8][9].…”
Section: Introductionmentioning
confidence: 99%